Implementasi Perjanjian Internasional dalam Penyelesaian Sengketa Batas Laut Zona Ekonomi Eksklusif antara Indonesia dan Vietnam - Rifda Ayu Akmaliya; Ida Ayu Rosida; Ega Permatadani; Sonia Amelia; Anang Dony Irawan (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
This study examines the actions or implementation of international treaty policies in resolving maritime boundary disputes of the Exclusive Economic Zone between Indonesia and Vietnam. The main cause of this dispute is a conflict of interest and goals. because the location of the sea boundaries between the two countries is very strategic. The purpose of this study is to determine the policy of the Indonesian state in resolving dispute cases with Vietnam related to the boundaries of the Exclusive Economic Zone based on regional law and international law, knowing the role of international agreements in resolving disputes. The method used is normative juridical research with a statutory approach and analyzing primary and secondary legal sources. The results of this study indicate that Indonesia-Vietnam resolves disputes through peaceful means, namely by means of mediation and negotiation in which each country agrees to determine maritime boundaries and bind itself in accordance with the basic role of international law of the sea, international agreements regarding bilateral cooperation relations from various fields.